Exploration of students’ errors in solving PISA problems on the uncertainty and data content - Mario David Turnip; Feri Tiona Pasaribu; Duano Sapta Nusantara (S&Co Publishing, 2025)
Indonesian students’ relatively low performance in PISA has been closely linked to their difficulties in applying mathematical knowledge to real-world contexts, which often led to errors. The main objective of this study was to explore the types of mistakes students made when solving PISA-type questions within the content area of uncertainty and data. This research was qualitative descriptive in nature. The research subjects consisted of five ninth-grade students from a junior high school in Jambi Province, selected based on teacher recommendations. Data were collected through tests and interviews. The results of the study showed that students frequently made mistakes at the stage of writing the final answer, primarily due to difficulties in interpreting the given information and focusing too heavily on calculation procedures while overlooking what the problem was actually asking. These findings provide a basis for further research on analyzing students’ mathematical literacy skills in solving PISA questions, particularly within the domain of uncertainty and data.